2018
DOI: 10.1111/jace.15982
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating ceramics with embedded microchannels using an integrated additive manufacturing and laser machining method

Abstract: In this paper, we demonstrate the feasibility of an innovative method to fabricate flexibly embedded microchannels in bulk ceramics of complex geometries. This innovative method is an integration of extrusion freeforming (EFF) and picosecond (PS) laser machining. The bulk ceramic green body of complex geometries was fabricated using the extrusion method. After one green layer was extruded, in‐plane microchannels with variable cross‐section sizes and aspect ratios were fabricated using a picosecond laser. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Usually, the paste extrusion flow rate Q is 0.3 mL/min, and the stage moving speed v is 15 mm/s. Under these conditions, a filament with a width d of ≈740 µm can be obtained according to the following, Equation (1) [34]:…”
Section: Microextrusion-based 3d Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the paste extrusion flow rate Q is 0.3 mL/min, and the stage moving speed v is 15 mm/s. Under these conditions, a filament with a width d of ≈740 µm can be obtained according to the following, Equation (1) [34]:…”
Section: Microextrusion-based 3d Printingmentioning
confidence: 99%
“…The L3DP system allows us to do advanced manufacturing of green or sintered ceramic parts easily by combining the 3D printing based on fast microextrusion, accurate subtractive manufacturing based on laser processing, and in-situ consolidation based on high-energy laser sintering. Starting from paste preparation from ball-milled precursor powders [33], by using the L3DP system, we can do the microextrusion-based 3D printing [34], rapid laser drying, rapid sintering, precise laser polishing, and precise laser cutting for the advanced manufacturing of PC parts (Figure 1b-g). The details of each experimental operation are described in the following experimental sections.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hong et al demonstrated a ceramic microchannel structure produced by the extrusion freeforming method. 1 The extrusion free-forming, also called the ceramic robocasting method, was first developed by Honoring Dr. Mrityunjay Singh Dr. Joseph Cesarano at Sandia National Laboratories in 1988. 2 According to the data retrieved from the Web of Science, robocasting has since become one of the most popular AM methods for producing ceramic parts, as shown in Figure 1, which details the number of publications on different ceramic AM methods between 1970 and 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional manufacturing methods to obtain customer-designed and complex-shaped Si 3 N 4 parts always rely on slip casting and dry-pressing molding. With the increase of application elds of Si 3 N 4 parts, more and more complex-shaped products with high accuracy are needed, such as high temperature heat exchanger, nozzle and so on [3][4][5]. Because of high hardness and brittleness of Si 3 N 4 ceramic, conventional fabrication process is unable to produce these sophisticated Si 3 N 4 parts with high precision.…”
Section: Introductionmentioning
confidence: 99%